Smart photocat reactor for remote CECs removal - Nur Aina Mardhiah, Badrul Hisham; Rosmawati, Naim; Hairul Hisham, Ismail (2021)
The product powered by photovoltaic solar panel is an efficient system which can be remotely installed in any onsite location for CECs removal. Photocatalyts combined with superior adsorptive nanocomposite to degrade the contaminant from any source of wastewater at faster rate.